Ekonomický dopad likvidace odpadů v malé firmě v souvislosti s ochranou životního prostředí - Minaříková, Lucie (Vysoké učení technické v Brně. Fakulta podnikatelská, 2012)
Bakalářská práce se zabývá analýzou ekonomiky společnosti v oblasti nakládání a likvidace odpadů, které zde vznikají. Předmětem podnikání této organizace jsou služby zajišťující náhradní energetické zdroje a servis v oblasti telekomunikací.

The bachelor thesis focuses on economic analysis of company in the field of treatment and disposal of waste which is produced here. Subject of enterprise of this company is providing alternative energy resources service and service in the field of telecommunication.
Economic Influence of the Waste Disposal in the Small Company in Connection with Environment Protection
Keywords: odpad; životní prostředí; ekonomika; nakládání s odpady; likvidace odpadu; waste; environment; economy; waste treatment; waste disposal